IN THIS ISSUE (The Strategic Review for Southern Africa, 2020)
It is no news to anybody that the power structures in our world have considerably shifted during the last quarter of a century. Glasnost and the ultimate collapse of the Soviet Union towards the end of the 1980s brought an end to the bipolar world dominated by the East-West conflict and the Cold War since the aftermath of World War II. The end of the Soviet bloc also paved the way towards an appeasement strategy inthe Southern African sub-region. What was praised as "the end of history", meaning the ultimate victory of capitalism as the uncontested mode of production structuring societies (and classes), however, led to an only short-lived sole hegemony of the main Western powers and in particular the United States (US) during the 1990s. These were the days when 'good governance' became the terminology of a crusade against which regimes were measured and judged. The criteria were based on Western capitalist notions of development as conceptualised and imposed by the International Financial Institutions (IFIs). But as we know, little changed for many towards the better. The problem of affordable access to higher education, a demand erupting these days forcefully on South African campuses, was not least enhanced through policy recommendations in the 1990s, which neglected such investment in the social and intellectual capacity of countries and their people.1)While old conflicts were solved, new conflicts and ideologicalbattlefields emerged. The rise of China as the world's next superpower marked the beginning of the 21st century, and the shock waves sent through the world with 9/11 opened a new era of "war against terror", in which human rights were the first victim. Development and security became integral elements of a global governance system, which since the turn of the century set paradigmatic frameworks, first with the Millennium Development Goals and now with the Sustainable Development Goals, while continuous efforts to achieve agreed measures to curb carbon emissions and bring environmental degradation and climate change to a halt have remained futile efforts. The tokenism so far only shows that governments continue to remain loyal to their own agendas. Guided by such shortsightedness, they do not act in solidarity with humanity as an integral part of nature and habitat to increase the chances for survival. Profit maximisation at all costs remains the ultimate goal even if in the long term at too high a price.